The Analysis of Lampung Province Proverty in terms of Macroeconomic Variables - Nouvan, M. Ahadi; Nairobi, Nairobi; Aida, Neli; Gunarto, Toto; Suparta, I Wayan (International Journal of Economics, Business, and Entrepreneurship, 2023)
Promoting public welfare is one of the goals of national development. One of the success factors of development is the reduction of poverty. This study aims to analyze the effect of macroeconomic variables on poverty in Lampung in the period 2011-2021. With this type of quantitative research with secondary data. Using panel data in the form of time series (2011-2021) and Cross Section (15 Regencies/Cities). The data analysis method in this study uses Panel Data regression analysis assisted by EViews version 9.0 software. The results showed that there was a positive and insignificant effect between the GRDP rate and poverty, the open unemployment rate had a positive and significant effect on poverty, and the Human Development Index had a negative and significant effect on poverty in the province of Lampung.